PSYCHOLOGICAL AND PEDAGOGICAL CONDITIONS FOR IMPROVING THE SOCIAL COMPETENCE OF CHILDREN AGED 6-7 - Tanrbergenova , Dildora (Zamonaviy ilmiy yondashuvlar va texnologik taraqqiyotning ustuvor yo‘nalishlari, 2026)
This article is dedicated to the development of social competence in children aged 6-7 during the transition period from preschool to primary education. In the context of modern globalization, fostering social adaptation, communication, and cooperation skills in children is considered one of the most pressing tasks of the education system. In the course of the study, methods of systematic analysis, pedagogical observation, and psychodiagnostic testing were used to determine the level of social adaptation of children. Additionally, specially developed game technologies for correcting relationships within a children's team were tested in practice. The results showed that purposeful pedagogical conditions significantly increase the indicators of emotional intelligence and social responsibility in children. It has been proven that the psychological and pedagogical support system ensures the child's successful integration into a new social environment. The conclusion proposes methodological recommendations for improving the social competence of 6-7-year-old children.